Modified posterior pelvic exenteration for advanced ovarian malignancies: a single‐institution study of 35 cases. (6th July 2017) - Minar, Lubos; Felsinger, Michal; Rovny, Ivo; Zlamal, Filip; Bienertova‐Vasku, Julie; Jandakova, Eva
Abstract: Introduction: This study aimed to investigate the possible benefits of a complete cytoreduction in patients with advanced ovarian cancer and concomitant rectal invasion. Furthermore, we evaluated the morbidity associated with radical surgery. Material and methods: A retrospective analysis examined 35 women who underwent radical surgery in the form of modified posterior pelvic exenteration. Descriptive statistics, Kaplan–Meier survival curves and log‐rank test were used for statistical estimations. Surgical complications were analyzed using the Clavien–Dindo classification. Results: The analysis of survival in relation to residual disease assessed according to Sugarbaker confirmed an optimistic prognosis in patients with optimal debulking with a mean disease‐free survival period of 33.6 months in R0 patients, 19.6 months in R1 patients, and 14.3 months in R2 patients. A statistically significant difference in disease‐free survival ( p = 0.023) was observed between the R0 (without residual disease) and R1+2 (with residual disease) groups. Surgical complications occurred in 83% of patients, with early postoperative complications being most frequent (65.7%). While grade III–IV complications occurred in 37.7% of all patients, no cases of surgery‐associated mortality occurred. Conclusions: Modified posterior pelvic exenteration is a highly effective method for achieving optimal debulking in cases of advanced ovarian cancer with the direct invasion of the rectum. Modified posterior pelvic exenteration does not delay the beginning of complementary chemotherapy. However, it is necessary to take into account surgery‐related morbidity. As modified posterior pelvic exenteration represents an extremely invasive technique, the surgical plan and perioperative care should be personalized to address the individual medical and surgical conditions of each patient.